OTITIS EKSTERNA AKIBAT INFESTASI Otodectes cynotis PADA KUCING DOMESTIK LONG HAIR - Erfan Andrianto Aritonang; Nindya Kusumawati; Ady Kurnianto (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2020)
A two years old male cat domestic long hair was brought to the Tabby Pet Care clinic with the owner's complaint that the cat often scratches his right and left ears. The results of clinical examination showed scratching marks on the pinna, blackish yellow, wet, and smelly ear serumen on the ear canal. Investigations include microscopic examination of ear swabs and cerumen swab cytology. Ear swab examination results observed the presence of Otodectes cynotis and Otodectes cynotis eggs. The results of cytological examination of cerumen swabs using the rapid stain method were observed to have bacterial infections in the form of bacilli, coccus, and the presence of neutrophil infiltration. Based on clinical symptoms and the results of investigations, the patient was diagnosed with external otitis with a fausta prognosis. Treatment of otitis externa is carried out with topical therapy Ilium® ear drop. Therapy is carried out for seven days. On the eighth day the patient was declared cured and allowed to go home.